2021
DOI: 10.1186/s12985-020-01472-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization assay with SARS-CoV-1 and SARS-CoV-2 spike pseudotyped murine leukemia virions

Abstract: Background Virus neutralization by antibodies is an important prognostic factor in many viral diseases. To easily and rapidly measure titers of neutralizing antibodies in serum or plasma, we developed pseudovirion particles composed of the spike glycoprotein of SARS-CoV-2 incorporated onto murine leukemia virus capsids and a modified minimal murine leukemia virus genome encoding firefly luciferase. This assay design is intended for use in laboratories with biocontainment level 2 and therefore c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 17 publications
3
41
0
Order By: Relevance
“…Our data analysis is concordant with other studies reporting false-negative results from RT-PCR tests ranging up to 30% [ 4 ]. Several studies have already showed that the diagnostic efficacy between RT-PCR test kits for SARS-CoV-2 nucleic acid detection may differ significantly depending on the probes and primers used [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data analysis is concordant with other studies reporting false-negative results from RT-PCR tests ranging up to 30% [ 4 ]. Several studies have already showed that the diagnostic efficacy between RT-PCR test kits for SARS-CoV-2 nucleic acid detection may differ significantly depending on the probes and primers used [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the WHO and Chinese Center for Disease Control and Prevention (CDC), real-time PCR (RT-PCR) is considered the ‘gold standard’ method for detection of SARS-CoV-2 infection [ 3 ]. Nevertheless, studies have shown that RT-PCR is an error-prone method showing false-negative results rates from respiratory samples for SARS-CoV-2 ranging from 1% to 30% [ 4 ]. These diagnostic errors are related to a number of preanalytical and analytical factors, including the source of the sample, delays or inadequate storage conditions before arrival to the laboratory, possible errors of RNA extractions, as well as the different quality and sensitivity of detection kits [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that CXCL10/IP10 is absent in healthy individuals. However, it is detected in asymptomatic patients and is directly linked to disease severity ( 96 , 97 ), suggesting that early detection of chemokines can help control new outbreaks ( 98 ). Several clinical investigations involving autopsies have also provided evidence that thrombosis is an important consequence of hCoV diseases ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 test kits employed by our group supported the propagation of local Columbus, OH strains of SARS-CoV-2 from testing samples, confirming that our VTM formulation maintained infectious virions. In laboratory experiments, others have shown that live SARS-CoV-2 survives in similar VTM for at least 72 h at room temperature, and viral RNA can be detected by RT-PCR as long as 28 days post collection [ 6 , 7 ]. In agreement with this, OSUWMC has contributed numerous full genome sequences of SARS-CoV-2 obtained from our testing kit samples, and identified a Midwestern variant of concern [8] .…”
Section: Discussionmentioning
confidence: 99%